DOROTHY JOHNSON'S THEORY AND NANDA DIAGNOSTIC CLASSIFICATION: AN INTENSIVE CARE MODEL - Maria Bettina Camargo Bub; Silvana Alves Benedet (Universidade Federal do Paraná, 1996)
A conceptual framework and nursing process are presented, founded on Dorothy Johnson's "Theory of Man as a Behavioral System" and also on the Nor th American Nursing Diagnosis Association(NANDA) Diagnostic Classification. The present study was designed to be conducted next to adults admitted as patients to an Intesive Care Unit(ICU). The conceptual framework encompasses concepts of human being, stability/instability, environment and nursing. The nursing process has the following stages: Data colletion, diagnosis, nursing intervention and evaluation.